Indonesia Challenges in Maintaining National Identity in the Era of Globalisation - Aulya Putri, jihan; Arasy, Ashila; Nelwati, Sasmi (Hakamain: Journal of Sharia and Law Studies, 2023)
This study aims to analyse the challenges faced in maintaining national identity in the era of globalisation using sociological research methods. The era of globalisation is characterised by increased interactions between nations that lead to the spread of values, cultures and ideologies that can threaten the homogeneity of national identities. This research uses a qualitative approach with a case study method on several countries that have experienced significant changes in their national identity due to the influence of globalisation. Data were collected through in-depth interviews, participatory observation, and document analysis. The results show that globalisation has resulted in cultural transformation, a shift in traditional values, and an increase in multiculturalism that challenges the integrity of national identity. In addition, information and communication technology also plays a major role in spreading global culture. The study concludes that effective strategies for maintaining national identity involve education that emphasises local values, cultural policies that support diversity, and strengthening local communities. Recommendations include the need for cooperation between the government, society and educational institutions in an effort to maintain and strengthen national identity amidst globalisation.